Intranational University Student Mobility: A Case Study of Student Migration and Graduate Retention in Eastern Canada - Kirby, Dale (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2021)
While international student mobility has received much examination, intranational student mobility is a lesser-studied area. Data shows that residents of the four Easternmost Canadian provinces are more likely to travel outside of their home province to undertake university studies than other Canadians. Beginning in the mid-1990s, Memorial University of Newfoundland experienced a near ten-fold increase in the enrolment of students from the three nearby Maritime provinces. Previous study of this enrolment trend indicated that the increase was partially driven by Memorial’s lower tuition fees. Guided by the conceptual lenses of student choice frameworks, tuition price sensitivity analyses, and student migration studies, this study was carried out to examine the persistence and graduation rates of the 2010 Maritime student cohort, where they resided following their university studies, and factors influencing their decisions to stay or leave Newfoundland and Labrador. This research primarily relied on university administrative records and participant survey responses. The results showed that almost 40% of the 2010 Maritime student cohort had dropped out two years after their initial enrolment at Memorial and by the sixth year, their graduation rate (45%) was far below the overall graduation rate for Canadian students in undergraduate degree programs (74%). In addition, almost 78% of those who were successfully surveyed in autumn 2020 were no longer residing in Newfoundland and Labrador. While there are limitations to the interpretation of the results, they raise important questions about tuition fee polices and their connection (or not) to population growth.